A Single Amino Acid Difference in Human APOBEC3H Variants Determines HIV-1 Vif Sensitivity - Zhen, Anjie (American Society for Microbiology (ASM), 2010)
Several variants of APOBEC3H (A3H) have been identified in different human populations. Certain variants of this protein are particularly potent inhibitors of retrotransposons and retroviruses, including HIV-1. However, it is not clear whether HIV-1 Vif can recognize and suppress the antiviral activity of A3H variants, as it does with other APOBEC3 proteins. We now report that A3H_Haplotype II (HapII), a potent inhibitor of HIV-1 in the absence of Vif, can indeed be degraded by HIV-1 Vif. Vif-induced degradation of A3H_HapII was blocked by the proteasome inhibitor MG132 and a Cullin5 (Cul5) dominant negative mutant. In addition, Vif mutants that were incapable of assembly with the host E3 ligase complex factors Cul5, ElonginB, and ElonginC were also defective for A3H_HapII suppression. Although we found that Vif hijacks the same E3 ligase to degrade A3H_HapII as it does to inactivate APOBEC3G (A3G) and APOBEC3F (A3F), more Vif motifs were involved in A3H_HapII inactivation than in either A3G or A3F suppression. In contrast to A3H_HapII, A3H_Haplotype I (HapI), which differs in only three amino acids from A3H_HapII, was resistant to HIV-1 Vif-mediated degradation. We also found that residue 121 was critical for determining A3H sensitivity and binding to HIV-1 Vif.